2020
DOI: 10.5194/bg-17-4261-2020
|View full text |Cite
|
Sign up to set email alerts
|

Linking tundra vegetation, snow, soil temperature, and permafrost

Abstract: Abstract. Connections between vegetation and soil thermal dynamics are critical for estimating the vulnerability of permafrost to thaw with continued climate warming and vegetation changes. The interplay of complex biophysical processes results in a highly heterogeneous soil temperature distribution on small spatial scales. Moreover, the link between topsoil temperature and active layer thickness remains poorly constrained. Sixty-eight temperature loggers were installed at 1–3 cm depth to record the distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 63 publications
9
79
2
Order By: Relevance
“…The dry and warm field season of 2018 might have amplified the difference in microclimatic conditions between lichens and shrubs. However, several studies across the Arctic or studies conducted in boreal forests reported similar results as in our study concerning the difference in microclimatic conditions between lichens and shrubs (Loranty et al, 2018b;Mikola et al, 2018;Grünberg et al, 2020). Moreover, the expansion of shrubs in general is associated with higher summer soil temperatures and atmospheric heating (Myers-Smith et al, 2011).…”
Section: Synthesissupporting
confidence: 87%
See 1 more Smart Citation
“…The dry and warm field season of 2018 might have amplified the difference in microclimatic conditions between lichens and shrubs. However, several studies across the Arctic or studies conducted in boreal forests reported similar results as in our study concerning the difference in microclimatic conditions between lichens and shrubs (Loranty et al, 2018b;Mikola et al, 2018;Grünberg et al, 2020). Moreover, the expansion of shrubs in general is associated with higher summer soil temperatures and atmospheric heating (Myers-Smith et al, 2011).…”
Section: Synthesissupporting
confidence: 87%
“…Shrubs benefit from recent climate change, since the higher temperatures and longer growing seasons are in favor of their growing conditions (Myers-Smith et al, 2011, 2020. Indeed, many studies found an increase in shrub cover, biomass, and abundance in alpine and Arctic areas over the past decades (Sturm et al, 2001b;Hallinger et al, 2010;see Myers-Smith et al, 2011, for a review). Such an increase in shrubs alters the vegetation composition in these areas (Pajunen et al, 2011;Boscutti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3.5). Shrub expansion can have multi-directional hydrological impacts (Grünberg et al, 2020), including shrub-snow interactions (Sect. 3.2) and increasing ET (Sect.…”
Section: Northern Vegetation Wildfire and Loss Of Ecological Resiliencementioning
confidence: 99%
“…Background Snow cover exerts a fundamental control on the thermal and hydrological regime of permafrost. It acts as an insulator thanks to its low thermal conductivity, reducing heat loss in winter (Zhang, 2005;Grünberg et al, 2020). The type of vegetation cover can significantly influence the insulating power of snow as plants affect the distribution of snow and its depth (Domine et al, 2018).…”
Section: Snowmentioning
confidence: 99%
“…However, two additional factors have to be considered when using maximum thaw depth as an indicator of permafrost response to climate conditions. Firstly, the maximum annual thaw depth varies from year to year in response to interrelated variables such as soil moisture, vegetation, and snow (e.g., Walker et al, 2003;Shiklomanov et al, 2010;Grünberg et al, 2020). Secondly, the thawing of icerich permafrost primarily induces subsidence rather than increases in thaw depth (Osterkamp et al, 2009;O'Neill et al 2019).…”
Section: Introductionmentioning
confidence: 99%